Analisis Kemampuan Tahsin dan Tahfizh Mahasiswa Matematika, Ilmu Pengetahuan Alam (MIPA) dan Pendidikan Agama Islam (PAI) - Sugilar, Hamdan; Dedih, Ujang; Anwar, Cecep; Darmalaksana, Wahyudin (Laboratory of Islamic Religious Education Faculty of Tarbiyah and Teacher, 2020)
The development of human character and personality, especially students, is one of them through the tahsin and tahfizh programs. This study aims to find out how the tahsin and tahfizh unit program and the ability of tahsin, tahfizh students majoring in Mathematics and Natural Sciences and Islamic Education. This research method is a qualitative descriptive study with the subject of 2015 student research majoring in PAI and MIPA tarbiyah and teacher training faculties in one of the in a college in the city of Bandung.. The results of the research show that the activities of tahsin and tahfizh are managed by the tahsin and tahfizh units of the faculty by involving supervisors and examiners of tahsin and tahfizh, the ability of tahsin and tahfizh of PAI and MIPA students in the good category with an average of 83.51 and tahfizh 84, 16 Students really respond to the existence of the units of tahsin and tahfizh and do not object to the obligation to memorize juz 30 as a condition of the munaqosah exam.Pengembangan karakter dan kepribadian manusia khususnya mahasiswa, salah satunya melalui program tahsin dan tahfizh. Penelitian ini bertujuan untuk mengetahui bagaimana program unit tahsin dan tahfizh dan kemampuan tahsin, tahfizh mahasiswa jurusan MIPA dan PAI. Metode penelitian ini merupakan penelitian deskriptif kualitatif dengan subjek penelitian mahasiswa angkatan 2015 jurusan PAI dan MIPA fakultas tarbiyah dan keguruan salah satu perguruan tinggi di Bandung. Adapun hasil penelitian menunjukkan bahwa kegiatan tahsin dan tahfizh dikelola oleh unit tahsin dan tahfizh fakultas dengan melibatkan dosen pembimbing dan penguji tahsin dan tahfizh, kemampaun tahsin dan tahfizh mahasiswa jurusan PAI dan MIPA pada kategori baik dengan rata-rata tahsin 83,51 dan tahfizh 84,16. Mahasiswa sangat merespon adanya unit tahsin dan tahfizh dan tidak keberatan dengan kewajiban menghapal juz 30 sebagai syarat sidang munaqosah.